Redefining the stress cortisol response to surgery. - Khoo,B; Boshier,PR; Freethy,A; Tharakan,G; Saeed,S; Hill,N; Williams,EL; Moorthy,K; Tolley,N; Jiao,LR; Spalding,D; Palazzo,F; et al. (Clinical Endocrinology, 2017)
BACKGROUND: Cortisol levels rise with the physiological stress of surgery. Previous studies have used older, less-specific assays, have not differentiated by severity or only studied procedures of a defined type. The aim of this study was to examine this phenomenon in surgeries of varying severity using a widely used cortisol immunoassay. METHODS: Euadrenal patients undergoing elective surgery were enrolled prospectively. Serum samples were taken at 8 am on surgical day, induction and 1 hour, 2 hour, 4 hour and 8 hour after. Subsequent samples were taken daily at 8 am until postoperative day 5 or hospital discharge. Total cortisol was measured using an Abbott Architect immunoassay, and cortisol-binding globulin (CBG) using a radioimmunoassay. Surgical severity was classified by POSSUM operative severity score. RESULTS: Ninety-three patients underwent surgery: Major/Major+ (n = 37), Moderate (n = 33) and Minor (n = 23). Peak cortisol positively correlated to severity: Major/Major+ median 680 [range 375-1452], Moderate 581 [270-1009] and Minor 574 [272-1066] nmol/L (Kruskal-Wallis test, P = .0031). CBG fell by 23%; the magnitude of the drop positively correlated to severity. CONCLUSIONS: The range in baseline and peak cortisol response to surgery is wide, and peak cortisol levels are lower than previously appreciated. Improvements in surgery, anaesthetic techniques and cortisol assays might explain our observed lower peak cortisols. The criteria for the dynamic testing of cortisol response may need to be reduced to take account of these factors. Our data also support a lower-dose, stratified approach to dosing of steroid replacement in hypoadrenal patients, to minimize the deleterious effects of over-replacement.